LIVER DYSFUNCTION IN DIABETIC PATIENTS ADMITTED IN REFERRAL HOSPITAL - Takhelmayum, Roshan; Thanpari, C.; Singh, T. Paras (BALI MEDICAL JOURNAL, 2014)
Background: Liver function tests (LFTs) are group of tests that help in diagnosis, monitoring therapy, and assessing prognosis of liver disease. To estimate liver function tests in diabetic patients attending OPD of Central Referral Hospital, Sikkim, India. Methods: This study was conducted in Central Referral Hospital, Gangtok, Sikkim, India between October 2007 to April 2008. A total of 150 diabetic patients and 50 controls were taken to assess the liver function tests (LFTs) by measuring Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Alkaline phosphatase (ALP) & total bilirubin (TB). Results: Total Bilirubin (TB) was found to be elevated in maximum number of patients, 84 (56%) out of 150 patients and followed by both AST and ALT, 39 (26%) each out of 150 patients. Conclusion: LFTs in type-2 diabetic patients are found to be statistically significant when compared with normal healthy controls.